RESULTS IN THE SURGICAL TREATMENT OF SMALL CELL CARCINOMA OF THE THYROID GLAND - Русин, В.І. (World of Medicine and Biology, 2015)
The analysis of the results of a comprehensive examination (ultrasound + cytology) in patients with carcinoma of the thyroid gland size to 1.0 cm. The results of pathomorphological, cytological and ultrasound findings were compared, evaluated the aggressive properties of malignant thyroid size units to 1cm. Determined the frequency of regional metastases and multifocal growth among patients who live in endemic areas.